2021
DOI: 10.1021/acs.jafc.1c03621
|View full text |Cite
|
Sign up to set email alerts
|

Cornflower Honey as a Model for Authentication of Unifloral Honey Using Classical Methods Combined with Plant-Based Marker Substances Such as Lumichrome

Abstract: According to legislation, unifloral honeys are characterized by their organoleptic, physicochemical, and microscopic properties. Melissopalynology is the established method for identifying the pollen taken up with the floral nectar by forager bees and is used for authentication of the nectar sources in honey. For cornflower honey (Centaurea cyanus), the pollen input does not correlate with the nectar input, because the nectar is produced both in floral and in extrafloral nectaries. The well-known cornflower ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…In previous studies, riboflavin and lumichrome are sporadically observed in honeys such as sage honey, cornflower honey, yellow sweet clover honey, and kanuka honey. This study shows that riboflavin, lumiflavin, and lumichrome are also present in safflower, Chinese sumac, and bauhinia honey; most notably, this is the first study to our knowledge to report the simultaneous presence of riboflavin, lumichrome, and lumiflavin in honeys. Moreover, the average content of lumichrome was much higher than those in thistle and sage honeys, , but similar to that in cornflower honey. , The higher average content of riboflavin in safflower honey is similar to that in thistle honey . We speculate that riboflavin, lumiflavin, and lumichrome may be responsible for the bright-yellow color of honeys.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In previous studies, riboflavin and lumichrome are sporadically observed in honeys such as sage honey, cornflower honey, yellow sweet clover honey, and kanuka honey. This study shows that riboflavin, lumiflavin, and lumichrome are also present in safflower, Chinese sumac, and bauhinia honey; most notably, this is the first study to our knowledge to report the simultaneous presence of riboflavin, lumichrome, and lumiflavin in honeys. Moreover, the average content of lumichrome was much higher than those in thistle and sage honeys, , but similar to that in cornflower honey. , The higher average content of riboflavin in safflower honey is similar to that in thistle honey . We speculate that riboflavin, lumiflavin, and lumichrome may be responsible for the bright-yellow color of honeys.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the average content of lumichrome was much higher than those in thistle and sage honeys, 28,32 but similar to that in cornflower honey. 29,33 The higher average content of riboflavin in safflower honey is similar to that in thistle honey. 32 We speculate that riboflavin, lumiflavin, and lumichrome may be responsible for the brightyellow color of honeys.…”
Section: Discussionmentioning
confidence: 69%
“…As the main functional components in honey, metabolites crucially contribute to the effects of health benefits of honey . Besides, establishing honey authenticity identification methods based on characteristic phytogenic components has become the object of multiple studies. , Thus, UHPLC-Q-TOF-MS/MS-based metabolomic analysis was conducted to screen characteristic phytogenic components that can discriminate between MH- Sco and other honeys. The methanol extracts from honey were subjected to UHPLC-Q-TOF-MS/MS after filtering, which is a more rapid and simpler sample pretreatment method compared with previous studies in determining metabolites …”
Section: Resultsmentioning
confidence: 99%